Peran Pemerintah Terhadap Peningkatan Rumah Layak Huni Melalui Program Bantuan Stimulan Perumahan Swadaya Guna Menunjang Pembangunan Ekonomi Berkelanjutan - Dias Sekarwati; Riko Setya Wijaya (Politeknik Kampar, 2023)
The house is a reflection of the life of the community because the house is a place to live where every community can be protected from various weather and diseases. However, the low level of public awareness of proper housing is still very low, this is due to economic factors that make the people themselves indifferent to proper housing. As is well known, sustainable development (SDGs) is an agreement taken by each country to improve the welfare of the community. This study uses a qualitative research method based on a case study approach to determine the role played by the government in improving livable housing to support sustainable economic development. The purpose of this study is to measure how effective the role of the Self-Help Housing Stimulant Assistance program is in increasing livable housing to support sustainable economic development.